COUNSELING ON COMMUNICATION DEVELOPMENT AND APPLICATION OF INCLUSIVE EDUCATION FOR CHILDREN WITH SPECIAL NEEDS - Purnama Sari, Desak Made Febri; Oka Martini, Ida Ayu; Bellinda Octavia, Vania (LPPM Univ. Ibn Khaldun Bogor, 2024)
In public elementary schools, students with special needs often find it difficult to participate in the learning process. Implementation of inclusive education is hampered by various causes. Examining how inclusive education is implemented in elementary schools for students with special needs is the aim of this research. This research methodology uses a library research strategy. methods for collecting data and information through a literature survey. According to research findings, inclusive education for children with special needs has been offered in elementary schools. When considering preparedness, however, it is still not the best because there are still too few teachers with the necessary training, which creates many difficulties and obstacles in guiding children with special needs. It can be concluded that there are still relatively few accompanying teachers with special needs with undergraduate backgrounds in the Special Education Study Program based on an examination of various relevant research papers. In conclusion, the majority of inclusive educational institutions mandate mentoring training for students with needs